2021
DOI: 10.3389/fpsyg.2021.635110
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Cultural Bayesian Network Analysis of Factors Affecting Residents’ Concerns About the Spread of an Infectious Disease Caused by Tourism

Abstract: COVID-19 has had a severe impact globally, and the recovery can be characterized as a tug of war between fast economic recovery and firm control of further virus-spread. To be prepared for future pandemics, public health policy makers should put effort into fully understanding any complex psychological tensions that inherently arise between opposing human factors such as free enjoyment versus self-restriction. As the COVID-19 crisis is an unusual and complex problem, combinations of diverse factors such as hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…For example, as individuals’ attitudes and behaviors to a crisis are strongly connected with personal values [3 , 8] , norms, and beliefs [4 , 9] , the questionnaire included questions about individuals’ personal values [3] , [8] , [10] , perceived risk [11] and their associated attitudes and behavioral intentions [12 , 13] . The implication of some of these theoretical concepts has been elaborated and analyzed in [1] . Supplementary materials accessible in [2] include a coded master questionnaire in English and its translation to Chinese, Danish, Italian and Japanese.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as individuals’ attitudes and behaviors to a crisis are strongly connected with personal values [3 , 8] , norms, and beliefs [4 , 9] , the questionnaire included questions about individuals’ personal values [3] , [8] , [10] , perceived risk [11] and their associated attitudes and behavioral intentions [12 , 13] . The implication of some of these theoretical concepts has been elaborated and analyzed in [1] . Supplementary materials accessible in [2] include a coded master questionnaire in English and its translation to Chinese, Danish, Italian and Japanese.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…After the cleaning the complete data delivered by You Gov were China ( n = 1,019), Denmark ( n = 1,028) and Italy ( n = 1,014), and by Cross Marketing was Japan ( n = 1,111). Data source location Institution: YouGov City/Town/Region: Copenhagen Country: Denmark Institution: Cross Marketing Inc. City/Town/Region: Tokyo Country: Japan Data accessibility Repository name: [Zenodo] Data identification number: [DOI: 10.5281/zenodo.5176085 ] Direct URL to data: [ https://zenodo.org/record/5176085#.YSFSlo4zZPZ ] Related research article Selected variables in this dataset have been filtered, analyzed, and presented in [1] : Glückstad F.K., Wiil U.K., Mansourvar M. and Andersen P.T. (2021) Cross-Cultural Bayesian Network Analysis of Factors Affecting Residents’ Concerns About the Spread of an Infectious Disease Caused by Tourism.…”
Section: Specifications Tablementioning
confidence: 99%
“…ey conclude that "group-oriented and collectivist values and low egalitarianism values" contributed favorably to COVID-19 fatality. Following a cross-cultural Bayesian analysis, Kano Glückstad et al [24] found that cultural values shape healthcare indicators depending on degree of local infections; pleasure seeking differently modulates the anxiety toward infection according to culture.…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…However, compared to the people without depressive disorder, researchers found a simpler network of community structure for the people with depressive disorder. Through building a multi-cultural Bayesian network, researchers (Glückstad et al 2021) found Japanese peoples' anxiety about the risk of COVID hotspots.…”
Section: Introductionmentioning
confidence: 99%